Characterizations of tripotents in JB*-triples - Hügli, Remo V. (MATHEMATICA SCANDINAVICA, 2006)
The set U(A) of tripotents in a JB^*-triple A is characterized in various ways. Some of the characterizations use only the norm-structure of A. The partial order on U(A) as well as σ-finiteness of tripotents are described intrinsically in terms of the facial structure of the unit ball A_1 in A, i.e. without reference to the (pre-)dual of A. This extends similar results obtained in [6] and simplifies the metric characterization of partial isometries in C^*-algebras found in [1](cf. [8].